Analisis Productivity PC 300 pada Kegiatan Coal Getting di PT. Asmin Bara Bronang - Maura Rahmawati; Yustinus Hendra Wiryanto; Yos David Inso; Hepryandi Luwyk Djanas Usup; Asri Fridtriyanda (Pusat riset dan Inovasi Nasional, 2026)
This study was conducted at PT. Asmin Bara Bronang, Sepan Uring Village, Kapuas Tengah District, Kapuas Regency, Central Kalimantan Province, with the aim of analyzing the productivity and influencing factors of the PC 300 excavator in coal getting activities to support the achievement of production targets. The objective of this research is to analyze the actual productivity and the factors affecting it in Sector 7 coal getting operations. The research method used field observation with a quantitative descriptive analysis approach. The results show that the productivity of the PC 300 excavator ranges from 127.12 to 224.29 tons/hour, with an average of 173.98 tons/hour. In several conditions, the productivity is still below the company’s target of 180 tons/hour. The analysis indicates that productivity is influenced by material conditions, particularly the Hardgrove Grindability Index (HGI) value of 47, which reflects relatively harder material with coarser particle size, and a moisture content of 22.71%, causing the material to be sticky and cohesive, thereby affecting the bucket filling process. In addition, operational factors such as bottom loading patterns, limited number of tailgate dump trucks, and suboptimal selection of dump truck types also contribute to productivity performance. Based on the findings, it can be concluded that the productivity of the PC 300 excavator has not consistently met the company’s target. Therefore, improvement efforts are required, including the implementation of top loading methods, increasing the number of tailgate dump trucks, optimizing the selection of hauling equipment, and controlling material conditions that affect the digging process.